Pengaruh Pajak Pendapatan Progresif (Pajak Penghasilan Pribadi) Terhadap Kesinambungan Fungsi - Dedek Kustiawati Kustiawati; Amalia Nurofah Nurofah; Arini Eka Sapitri; Ricky Delfianto Delfianto (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This research is a type of research that uses descriptive methods, library research approaches or library research to analyze the effect of continuity on the progressive income tax function, namely personal income. In this study, a discussion of the 2018 income tax rate and the 2021 income tax rate shows that the income tax function in income tax is included in the discontinuous function. This is evidenced through the proof that is carried out using the concept of continuity and continuity graphs. This study proves that regulations or provisions regarding income tax rates from 2018 and 2021 do not affect the sustainability of the function, but the range or categorization of the tax provisions affect the sustainability function.